Risk factors of severe heart failure in HIV-positive patients - O. G. Goryacheva; N. A. Koziolova (Российский кардиологический журнал, 2021)
Aim. To study the relationship of N-terminal pro-brain natriuretic peptide (NT-proBNP) with clinical symptoms, structural and functional cardiac abnormalities in human immunodeficiency virus (HIV)-positive patients with heart failure (HF), as well as to identify risk factors for severe HF.Material and methods. During the year, 150 HIV-positive patients with typical symptoms and signs of stable HF were examined in the hospital. Among them, HF, confirmed by structural and functional cardiac changes and NT-proBNP increase above 125 pg/ml, was identified in 83 (55,3%) patients. These patients were divided into 3 groups depending on the blood concentration of NT-proBNP: group 1 (n=54) — patients with NT-proBNP of 125-700 pg/ml; group 2 (n=12) — patients with NT-proBNP of 701-1500 pg/ml; group 3 (n=17) — patients with NT-proBNP >1500 pg/ml.Results. As NT-proBNP increased in HIV-positive patients with HF, the left ventricular (LV) ejection fraction (EF) significantly decreased (p=0,005). Also, the increase in the severity of HF symptoms (p<0,001), prevalence of chronic kidney disease (CKD) (p<0,001), chronic hepatitis B and/or C (p=0,011), prior infective endocarditis (p=0,002), thromboembolic events (p=0,007), chronic obstructive pulmonary disease (p=0,016), pneumonia (p=0,002) and inflammatory diseases during hospitalization (p=0,002), severe thrombocytopenia (p=0,032). We revealed significant differences between the groups in the frequency of decreased cluster of differentiation antigen 4 (CD4) <200 cells/pl (p=0,013).Conclusion. In HIV-positive patients with clinical symptoms of HF, the prevalence of its verification in accordance with Russian guidelines (2020) was 55,3%. In 62,7% of HIV-positive patients with HF, preserved EF was detected. Among the comorbidities, 9 risk factors of severe HF in HIV-positive patients with NT-proBNP >1500 pg/ml were identified. With CKD and inflammatory diseases during hospitalization, the relative risk of severe HF in patients with HIV infection is increased by more than 6 times, while with thromboembolic events — 5,3 times, infective endocarditis — 4,4 times, pneumonia during hospitalization and severe thrombocytopenia — more than 3,5 times, chronic obstructive pulmonary disease — 2,1 times, chronic hepatitis B and/or C — 1,7 times. As HIV infection progresses (CD4 <200 cells/pL), the risk of severe HF increases 1,6 times.